1993
DOI: 10.1111/j.1464-410x.1993.tb00737.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Two‐stage Orchiopexy on Testicular Growth

Abstract: Testicular growth was measured in 33 males who had undergone 2 orchiopexies on the developing testis. Multiple surgery on the abdominal or canalicular testis was associated with a high rate of testicular atrophy (40%) and a 46% decrease in testicular volume. A similar decrease (43%) in testicular volume was noted in those patients with an infracanalicular testis but no testis atrophied in this group. The results suggest that primary orchiectomy be considered in the high testis provided the contralateral testis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
1
Order By: Relevance
“…However, can it be considered as normal if the testis reveals normal or mild decreased volume after SVCD procedure? It has been observed that 40% of the testes were atrophied and 48% were volume decreased in addition after two-staged orchidopexy [19], in which the authors did not confirm whether the decreased volume of testes was considered to be atrophy. In the present study, apart from the atrophic testes with evident size reduction, only 15% SVCD testes showed normal histology; 34% SVCD testes revealed normal or mild size reduction, but evidently decreased ST area and Johnsen score with partial (24%) or severe (10%) impaired spermatogenesis from peripuberty to middle age.…”
Section: Discussionmentioning
confidence: 92%
“…However, can it be considered as normal if the testis reveals normal or mild decreased volume after SVCD procedure? It has been observed that 40% of the testes were atrophied and 48% were volume decreased in addition after two-staged orchidopexy [19], in which the authors did not confirm whether the decreased volume of testes was considered to be atrophy. In the present study, apart from the atrophic testes with evident size reduction, only 15% SVCD testes showed normal histology; 34% SVCD testes revealed normal or mild size reduction, but evidently decreased ST area and Johnsen score with partial (24%) or severe (10%) impaired spermatogenesis from peripuberty to middle age.…”
Section: Discussionmentioning
confidence: 92%
“…Staged orchidopexy was an option considered previously in high inguinal testis [8]. However, it was associated with a high rate of testicular atrophy in up to 40% of the cases [9].…”
Section: Discussionmentioning
confidence: 99%
“…Also higher rates of postoperative atrophy, up to 40%, have been reported, but these were associated with staged orchidopexies [84, 85]. Thus, nonpalpable testes are at a higher risk of being damaged than palpable ones.…”
Section: Untoward Effects Of the Treatmentmentioning
confidence: 99%